THE IMPACT OF LÈSE MAJESTÉ LAWS AND AUTHORITARIAN RULE ON DEMOCRACY IN THAILAND - Sigit; Setiawan , Theofilus Jose; Elizabeth (Malaysian Journal of International Relations, 2025)
This paper aims to analyse the impact of lèse-majesté and authoritarian regimes on Thailand using the distribution of power as the conceptual framework. Thailand’s contemporary political landscape reflects a persistent tension between constitutional democracy and entrenched authoritarian structures. Although formally a constitutional monarchy, the country continues to rely on legal and military instruments that suppress political participation. A central element in this dynamic is the lèse-majesté law, as defined in Article 112 of the Thai Penal Code, which criminalizes criticism of the monarchy and has been used to curb political expression, particularly during periods of military influence in government. The enforcement of this law has narrowed civic space, curtailed freedom of expression, and fostered an environment that suppresses public debate and political contestation. At the regional level, these domestic conditions intersect with broader governance challenges in Southeast Asia, where fragile institutions, historical legacies, and the ASEAN principle of non-interference have allowed authoritarian practices to persist. This paper suggests that democracy has made progress in parts of the region, however, Thailand’s experience illustrates how legal and political mechanisms can hinder further reform. In addition, the enduring obstacles through lèse-majesté and authoritarianism are still around in order to advance civil liberties and accountable governance both in Thailand and the region.